CONTENT OF HEAVY METALS IN THE SEA WATER OF THE NORTHERN CASPIAN SEA - M. S. Yessenamanova; D. Zhakyayeva; A. Ryszhan; Zh. S. Yessenamanova; А. Е. Tlepbergenova; A. Pendashteh (Academic Scientific Journal of Chemistry, 2021)
The article presents the results of chemical analysis for the content of heavy metals in the waters of the fields in the northern part of the Caspian Sea. The content of heavy metals in water is a complex and informative indicator of the degree of water pollution and can be used in environmental monitoring of water bodies. An analysis was carried out on the content of eleven heavy metals at the Kashagan, Kalamkas Kairan and Aktoty deposits for the period from 2006 to 2019. All results were averaged with indication of their minimum, maximum and average values, and were also compared with the MPC of these heavy metals. Among the eleven heavy metals, only one metal is characterized by a content below the MPC, this is barium. The barium content was determined by sweat in all samples, but at the same time they did not exceed the MPC in all samples. A slight excess of the MPC is typical for such metals as cadmium, arsenic and zinc. Almost in all samples, except for one sample, cadmium was found, but at the same time it did not exceed 0.3 MPC. The maximum value was determined in samples from the Kashagan field. Arsenic was found only in 3.4% of samples, mainly in deep-water areas of the Kalamkas field, in which the content did not exceed 1.3 MPC. The zinc content was found in most samples with no excess of more than 0.3 MPC. The rest of the elements are high and highly high in content such as mercury, lead, vanadium, chromium, copper, nickel, and iron. The content of mercury was found in the samples over 1%, but with an excess of 10 to 47 MPC. The content of lead was found in the samples over ten percent, with an excess of 11 to 60 MPC. Vanadium was found in samples of about 20%, with an excess in the range of 2-6 MPC. Chromium was found in most samples with an excess of 3 to 29 MPCs at Kalamkas in 2014 and Kashagan in 2019. Copper content was found in samples of about 90%, with high concentrations at Kashagan in 2006 and 2010 up to 10-38 MPC. Nickel is found in most samples with a level of 0.9-1.1 MPC. The content of iron was found in more than 10 percent of samples with an excess of 15- 60 MPC with a decrease of almost 3 times from 2006-2010 to 2011-2019